Stepwise strategic environmental management in marine protected area - A. Padash; S.A. Jozi; S.M.B. Nabavi; B. Dehzad (Global Journal of Environmental Science and Management)
In recent decades, necessity to protect environment has been a serious concern for all people and international communities. In appropriate development of human economic activities, subsistence dependence of the growing world population on nature decreases the natural diversity of ecosystems and habitats day by day and provides additional constraints for life and survival of wildlife. As a result, implementation of programs to protect species and ecosystems is of great importance. The current study was carried out to implement a comprehensive strategic environmental management plan in the Mond protected area in southern Iran. Accordingly, the protected area was zoned using multi criteria decision method. According to the numerical models, fifteen data layer were obtained on a scale of 1:50,000. The results revealed that 28.35% out of the entire study area belongs to nature conservation zone. In the following step, in order to offer the strategic planning using strength, weaknesses, opportunities and threats method, a total number of 154 questionnaires were prepared and filled by the relevant experts. For this purpose, after identifying the internal and external factors, they were weighted in the form of matrices as; internal factor evaluation and external factor evaluation. Analytical hierarchy process and expert choice software were applied to weight the factors. At the end, by considering the socioeconomic and environmental issues, the strategy of using protective strategies in line with international standards as well as a strong support of governmental national execution with a score of 6.05 was chosen as the final approach.